Synthesis of the tetrasaccharide repeating unit of the O-specific polysaccharide of Azospirillum doebereinerae type strain GSF71T using linear and one-pot iterative glycosylations - Gucchait, Arin; Shit, Pradip; Misra, Anup Kumar (Beilstein Journal of Organic Chemistry, 2020)
A straightforward synthetic strategy was developed for the synthesis of the tetrasaccharide repeating unit corresponding to the O-specific polysaccharide of Azospirillum doebereinerae type strain GSF71T in a very good yield adopting sequential glycosylation followed by removal of the p-methoxybenzyl (PMB) group in the same pot. Further, the synthetic strategy was modified by carrying out three stereoselective iterative glycosylations followed by in situ removal of the PMB group in one pot. The stereochemical outcome of the newly formed glycosidic linkages was excellent using thioglycoside derivatives as glycosyl donors and a combination of N-iodosuccinimide (NIS) and perchloric acid supported on silica (HClO4-SiO2) as the glycosyl activator.
Keywords: Azospirillum doebereinerae; glycosylation; HClO4-SiO2; O-polysaccharide; tetrasaccharide